Identification and characterisation of homologous recombination genes in Schizosaccharomyces pombe - Moss, J (2011)
DNA double-strand breaks (DSBs) are highly genotoxic lesions, which can promote chromosomal rearrangements and tumorigenesis through oncogene activation or loss of heterozygosity (LOH) at tumour suppressor loci. To identify new genes involved in DSB repair and genome stability, an S. pombe deletion library was screened for mutants which exhibited sensitivity to the DNA damaging agents bleomycin and/or MMS. 192 mutants were isolated which exhibited increased sensitivity to one or both of these agents. These mutants were further analysed in a sectoring assay and mutants sought which exhibited elevated levels of break-induced loss and rearrangement of a non-essential minichromosome. Using this approach 57 genes were identified, including all known homologous recombination (HR) and DNA damage checkpoint genes present in the library. Further, quantitative analysis of DSB repair indicated that 25 of these genes functioned to promote efficient HR repair, thus representing a comprehensive HR gene set in fission yeast. Included in this gene set are 10 genes not previously implicated in HR repair; nse5⁺, nse6⁺, ddb1⁺, cdt2⁺, alm1⁺, snz1⁺, kin1⁺, pal1⁺, SPAC31G5.18c⁺ and SPCC613.03⁺. Detailed characterisation of ddb1Δ and cdt2Δ established a role for the Ddb1-Cul4Cdt2 ubiquitin ligase complex in HR. The findings presented here support a model in which break-induced Rad3 and Ddb1-Cul4Cdt2 ubiquitin ligase-dependent Spd1 degradation promotes ribonucleotide reductase activation and nucleotide biosynthesis, which is required for post-synaptic ssDNA gap filling during HR repair. Lastly, the role of HR genes in suppressing chromosome loss and rearrangements was examined. A striking inverse correlation between levels of gene conversion and levels of both chromosome loss and LOH was observed across the HR gene deletion set. These findings support a common and likely evolutionarily conserved role for HR genes in suppressing both chromosome loss and break-induced chromosomal rearrangements resulting from extensive end processing associated with failed HR repair.